2005
DOI: 10.1111/j.1365-2583.2005.00589.x
|View full text |Cite
|
Sign up to set email alerts
|

Cold hardening and transcriptional change in Drosophila melanogaster

Abstract: Cold hardening treatment - a brief exposure to low temperatures - can protect certain insects against subsequent exposure to temperatures sufficiently low to cause damage or lethality. Microarray analysis to examine the changes in transcript abundance associated with cold hardening treatment (0 degrees C for 2 h followed by 30 min recovery at 25 degrees C) was undertaken in Drosophila melanogaster in order to gain insight into this phenomenon. Transcripts associated with 36 genes were identified, a subset of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
177
3
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(190 citation statements)
references
References 42 publications
6
177
3
4
Order By: Relevance
“…However, it was also possible, using functionality of proteins derived from sequence similarity data to identify a potential shift from carbohydrate to fatty acid oxidative pathways during this process. A similar shift appears during hibernation and it is plausible that both cold hardening and hibernation may share similar mechanisms (Qin et al 2005). of Pyrrhocoris apterus exposed to constant low temperature (-5°C) suggesting a failure in the function of an active metabolic component (ion pump), which can result in dissipation of trans-membrane ion balance (Overgaard et al 2007).…”
Section: Mitochondrial Degradationmentioning
confidence: 76%
See 2 more Smart Citations
“…However, it was also possible, using functionality of proteins derived from sequence similarity data to identify a potential shift from carbohydrate to fatty acid oxidative pathways during this process. A similar shift appears during hibernation and it is plausible that both cold hardening and hibernation may share similar mechanisms (Qin et al 2005). of Pyrrhocoris apterus exposed to constant low temperature (-5°C) suggesting a failure in the function of an active metabolic component (ion pump), which can result in dissipation of trans-membrane ion balance (Overgaard et al 2007).…”
Section: Mitochondrial Degradationmentioning
confidence: 76%
“…This category includes the aquaporins. These genes were discovered as recently as 1992 by Agre et al (1993) Other approaches include the use of microarrays (Qin et al 2005), exploitation of genome data (Sinclair et al 2007) and proteomics (Colinet et al 2007). Only the latter investigated a non-model organism: the parasitic wasp (Aphidus colemani), whilst the others concentrated on Drosophila.…”
Section: Mitochondrial Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we only examined one time point, 20 min into recovery from the cold exposure, our data indicated a large increase in omega-c levels, and that this did not occur for the omega-n transcript. A temporal expression study during cold recovery in this species, as was recently performed by microarrays on which hsr-omega was not represented (Qin et al, 2005), is needed for both hsr-omega transcripts. We also found that constitutive levels of omega-n were reduced in replicate populations selected for cold tolerance, suggesting a role for omega-n in determining fitness following cold exposure.…”
Section: Hsr-omega-l Chromosomesmentioning
confidence: 99%
“…This RCH also preserves reproductive behavior (Shreve et al, 2004). The molecular underpinnings of Drosophila cold tolerance have been explored extensively via microarrays (Qin et al, 2005;Zhang et al, 2011), quantitative trait loci (QTL) (Morgan and Mackay, 2006;Gerken et al, 2015), RNA sequencing (MacMillan et al, 2016) and proteomics (Sørensen et al, 2017), yet surprisingly few genes are consistently upregulated or associated with low temperatures.…”
Section: Introductionmentioning
confidence: 99%